An experimental study on spray filled tower - Mohiuddin, A. K. M. (2002)
This paper deals with an experimental study of different parameters in a Spray Filled Tower. The pressure drop and drift loss characteristics of cellular type drift eliminators and also those made of wood and cement-asbestos were experimentally investigated. Air distribution at some specific points within the tower was also investigated. The experiments were conducted with two and three stages of both wooden drift eliminators (WDE) and cement-asbestos drift eliminators (CADE) with various orientation angle,  of the eliminator plates. But for cellular type drift eliminators (CTDE) the experiment was carried out with one, two and three stages. The results showed that the pressure drop and drift loss were strong functions of number of stages, n and air flow rate. In case of WDE and CADE they were strongly dependent on  as well.